Sitting volleyball players: differences in physical and psychological characteristics between national and league teams - Ahmadi, S.; Marszalek, J.; Gutierrez, G. L.; Uchida, M. C. (Kinesiology, 2020)
The aim of the present study was to describe and compare physical profiles and certain psychological aspects of sitting volleyball players in a national team and in a league team. Twenty-seven Brazilian sitting volleyball players (15 from the national team, 12 from the league team) took part in this study. They completed demographics, FANTASTIC, anthropometrics, handgrip, seated chest pass, modified agility T, modified speed and agility, and speed and endurance tests. Data were processed by Chi2-test, Mann-Whitney U test, Pearson correlation, and a stepwise multiple linear regression analysis. The national team players had significantly more training time and better lifestyle (p<.01) than the league players. Significant regression equation results for predicting players` level included weekly training volume and hip circumference (R2=.68). In conclusion, national team and league players differed in just psychological aspects and magnitude training time, which show the importance of psychological characteristics in elite sitting volleyball.